The Influence Of Spiritual Emotional Freedom Technique On Cortisol Levels in Ischaemic Stroke Patients - Nurahman Hendra Kusuma, Aria; Pudjonarko, Dwi; Sujianto, Untung (Poltekkes Kemenkes Surakarta, 2024)
Background: Ischaemic stroke patients experience an increase in cortisol of 38% over 90 days. The spiritual emotional freedom technique (SEFT) provides manual stimulation of acupuncture points, which makes the muscles feel relaxed so that they can control cortisol. This study set out to assess how SEFT affected the cortisol levels in patients who had suffered an ischaemic stroke. Methods: A control group and pre- and post-test measures were part of the quasi-experimental research design. There were seventy-one patients in the research population of the study. The sample was measured using the Slovin formula, and the sampling strategy used was purposeful sampling. Over the course of three months, the intervention group had 12 sessions of SEFT once a week, whereas the control group received regular spiritual treatment from RSUD Dr. Moewardi Surakarta, an outpatient nurse. The ELISA method was used to measure cortisol levels. The Kolmogorov-Smirnov test was used to assess normality, and the Levene test was used to test for homogeneity in bivariate data. The Mann-Whitney method was used to analyze the data. Results: The mean cortisol before intervention was 119.63, and the mean cortisol after intervention was 99.23. SEFT affects cortisol levels in patients who have had an ischaemic stroke, according to a statistically significant (p<0.05) p-value of zero. Conclusion: Patients with ischaemic stroke experienced a significant drop in cortisol levels after using the SEFT. Furthermore, it is necessary to study the dominant factors that influence the cortisol hormone and the need for a multi-religious approach in an effort to develop spiritual-based interventions.